Low-Energy Electron Irradiation of Tick-Borne Encephalitis Virus Provides a Protective Inactivated Vaccine - Finkensieper, Julia; Issmail, Leila; Fertey, Jasmin; Rockstroh, Alexandra; Schopf, Simone; Standfest, Bastian; Thoma, Martin; Grunwald, Thomas; Ulbert, Sebastian (Frontiers in Immunology, 2022)
Tick-borne encephalitis virus (TBEV) is a zoonotic flavivirus which is endemic in many European and Asian countries. Humans can get infected with TBEV usually via ticks, and possible symptoms of the infection range from fever to severe neurological complications such as encephalitis. Vaccines to protect against TBEV-induced disease are widely used and most of them consist of whole viruses, which are inactivated by formaldehyde. Although this production process is well established, it has several drawbacks, including the usage of hazardous chemicals, the long inactivation times required and the potential modification of antigens by formaldehyde. As an alternative to chemical treatment, low energy electron irradiation (LEEI) is known to efficiently inactivate pathogens by predominantly damaging nucleic acids. In contrast to other methods of ionizing radiation, LEEI does not require substantial shielding constructions and can be used in standard laboratories. Here, we have analyzed the potential of LEEI to generate a TBEV vaccine and immunized mice with three doses of irradiated or chemically inactivated TBEV. LEEI-inactivated TBEV induced binding antibodies of higher titer compared to the formaldehyde-inactivated virus. This was also observed for the avidity of the antibodies measured after the second dose, whereas both inactivation methods elicited similar titers of neutralizing antibodies. After viral challenge, the mice immunized with LEEI- or formaldehyde-inactivated TBEV were completely protected from disease and had no detectable virus in the central nervous system. Taken together, the results indicate that LEEI could be an alternative to chemical inactivation for the production of a TBEV vaccine.